Implementasi Kesenian Ronggeng Amen Berbasis Proyek Sebagai Pengenalan Budaya Lokal Dalam Ekstrakulikuler Seni Tari Di SMA Negeri 1 Mangunjaya Kabupaten - Rany Ismaya Agustin; Asti Tri Lestari; Budi Dharma (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study aims to describe the process and outcomes of implementing Ronggeng Amen traditional dance through Project Based Learning in extracurricular dance activities at SMA Negeri 1 Mangunjaya as a strategy for introducing local culture. This research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The research subjects included students participating in dance extracurricular activities and related parties involved in the program. Data analysis was conducted using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing with verification through triangulation. The findings indicate that the implementation of Project Based Learning in extracurricular dance activities effectively facilitates active student involvement in learning Ronggeng Amen. The project-based approach encourages students to understand Ronggeng Amen not merely as a sequence of dance movements, but as a cultural heritage with symbolic meanings and social functions. Furthermore, the implementation contributes to the improvement of students’ understanding of local culture, appreciative attitudes, active participation, as well as the development of collaboration and responsibility skills. Therefore, Project Based Learning is considered a relevant and effective strategy for introducing and preserving local culture through dance extracurricular activities.